Analysis of Pharmacokinetic Parameters of Acetylsalicylic Acid for Prediction of Potential Nephrotoxic Effects - L. M. Krasnykh; O. A. Goroshko; G. F. Vasilenko; G. I. Gorodetskaya; V. V. Smirnov; T. A. Rodina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
Nonsteroidal anti-inflammatory drugs, including acetylsalicylic acid, can have a dose-dependent nephrotoxic effect. The study of the pharmacokinetics of acetylsalicylic acid products will contribute to timely detection and correction of side effects caused by this medicinal product.The aim of the study was to evaluate potential nephrotoxic effects following a single oral administration of 75 mg of acetylsalicylic acid, based on the analysis of the pharmacokinetic parameters.Materials and methods: the study involved 24 healthy volunteers who received 75 mg of acetylsalicylic acid (tablets) once orally. The measurement of the active metabolite of acetylsalicylic acid-salicylic acid-in blood plasma was performed by HPLC/MS using an Agilent 1200 liquid chromatography system coupled to an Agilent 6140 tandem mass spectrometer. Agilent Eclipse XDB-C18 column (4.6 mm×150 mm; 5.0 μm) was used for chromatographic separation. The test procedure used in the study was validated. The results obtained were used to calculate the pharmacokinetic parameters: Cmax (maximum concentration), Tmax (time to maximum concentration), T1/2 (half-life of the drug), AUC0-t (area under the pharmacokinetic curve from 0 to the last time point of the curve), AUC0-∞ (total area under the pharmacokinetic curve from 0 to ∞), MRT (mean residence time of the drug in the blood), Kel (elimination rate constant), Cl/F (total clearance), Vd/F (apparent volume of distribution). The Statistics (22.0.0.0) software was used for statistical processing of the results.Results: T1/2 of salicylic acid in blood plasma was determined to be 1.6 ± 0.5 h, Cmax was 4523.0 ± 725.0 ng/mL, and Tmax was 0.98 ± 0.4 h. AUC0-t was equal to 16183.0 ± 3823.0 ng×h/m, Vd/F was 12.0 ± 3.1 L/kg, and MRT was 2.9 ± 0.6 h.Conclusions: the analysis of the pharmacokinetic parameters demonstrated a high absorption rate, intensive distribution, and moderate elimination rate of salicylic acid (the main metabolite of acetylsalicylic acid), indicating a low risk of nephrotoxic effects associated with the studied dose of the drug.